Analysis of Income Enhancement of Cattle in Karo Regency - Qoryna Khalida; Tavi Supriana; Ade Trisna (Randwick International of Social Science Journal, 2023)
The enhancement of the income of the s is expected to have an impact on the welfare of cattle breeders in Karo Regency. The focus of this paper is to decide the factors that influence the respondents’ income to grow Cattle business better in Karo Regency. It also was conducted in Tigapanah District, Tigabinanga District and Dolat Rakyat District in Karo Regency with using 78 respondents. The results showed that the cattle breeds, the feed, the labor and the selling cost of livestock were factors that had a notable result on the respondents’ income in Karo Regency, while the cages cost and other costs did not have a notable effect on the respondents’ income in Karo Regency.